ChemInform Abstract: Organocatalytic Enantioselective Synthesis of 1‐Vinyl Tetrahydroisoquinolines Through Allenamide Activation with Chiral Broensted Acids. Issue 26 (June 2015) - Manoni, E.; Gualandi, A.; Mengozzi, L.; Bandini, M.; Cozzi, P. G.
Abstract 1‐Vinyl tetrahydroisoquinoline ((R)‐II) is synthesized through a metal‐free strategy for a stereoselective Friedel—Crafts‐type cyclization reaction using an axial‐chiral phosphoric acid as catalyst.